Antimicrobial and antioxidant activities of triterpenoid and phenolic derivatives from two Cameroonian Melastomataceae plants: Dissotis senegambiensis and Amphiblemma monticola - Raissa Tioyem Nzogong; Fabrice Sterling Tchantchou Ndjateu; Steve Endeguele Ekom; Jules-Arnaud Mboutchom Fosso; Maurice Ducret Awouafack; Mathieu Tene; Pierre Tane; Hiroyuki Morita; Muhammad Iqbal Choudhary; Jean- (BMC, 2018)
Abstract Background Antimicrobial resistance is a serious threat against humankind and the search for new therapeutics is needed. This study aims to investigate the antimicrobial and antioxidant activities of ethanol extracts and compounds isolated from Dissotis senegambiensis and Amphiblemma monticola, two Cameroonian Melastomataceae species traditionally used for the treatment of fever, malaria and infectious diseases. Methods The plant extracts were prepared by maceration in ethanol. Standard chromatographic and spectroscopic methods were used to isolate and identify fourteen compounds from the two plant species [1-6 (from D. senegambiensis), 3, 4 and 7-14 (from A. monticola)]. A two-fold serial micro-dilution method was used to determine the minimum inhibitory concentration (MIC) against four bacterial strains including two resistant bacterial strains, methicillin resistant S. aureus (MRSA3) and methicillin resistant S. aureus (MRSA4) and three yeast strains. Results The fractionation of EtOH extracts afforded fourteen compounds belonging to triterpenoid and phenolic derivatives. The ethanol extracts, compounds 3, 5-8, 10 and the mixture of 10 + 12 were active against all the tested bacterial and fungal species. Compound 7 (MIC = 16-32 μg/mL) and 10 (MIC = 8-16 μg/mL) displayed the largest antibacterial and antifungal activities, respectively. Compounds 7, 10 and the mixture of 10 + 12 showed prominent antibacterial activity against methicillin- resistant S. aureus (MRSA) which is in some cases equal to that of ciprofloxacin used as reference antibacterial drug. Compound 8 also showed high radical-scavenging activities and ferric reducing power when compared with vitamin C and butylated hydroxytoluene used as reference antioxidants. The tested samples were non-toxic to normal cells highlighting their good selectivity. Conclusions The result of this investigation reveals the potential of D. senegambiensis and A. monticola as well as the most active compounds in the search for new antimicrobial and antioxidant agents. So, further investigations are needed.